Finding The Best Location for The Implementation of Organic Agriculture in The Plains of Jableh Area Using GIS - علوش, نجود; سمرة, بديع; الهوشي, بشار عبد الحليم (Latakia University Journal - Arts and Humanities Sciences Series, 2020)
The study was conducted on the plains of Jableh area between 2016 and 2018. It aims at identifying the lands that meet the conditions and requirements for organic agriculture. The researcher has worked to find the best location for the implementation of organic agriculture by limiting the basic organic agriculture standards associated with location, according to the Syrian organic agriculture law in collaboration with the organic production office, Then the locations where these standards meet have been identified using ArcGIS. A map showing these locations in the plains of Jableh area has been designed, and these areas have been measured. Then the required time for preparing them tobe used in organic agriculture has been measured using a map showing the types of current crops in these areas. As a result of this study, it has been shown that there are large areas with a percentage of 84.76% of agricultural land, and a percentage of 68.42% of the total area of the plains of Jableh area which is liable to be used for organic agriculture.